Science, quality and value of laboratory medicine: opinion paper - Plebani, Mario; Langlois, Michel; Meyer, Alexander von; Vermeersch, Pieter; Zaninotto, Martina; Smeets, Ruben L.; Padoan, Andrea; Cubukcu, Hikmet Can; Monaghan, Phillip J.; Coşkun, Abdurrahman; Orth, Matthias; Thelen, Marc (Clinical chemistry and laboratory medicine, 2026)
The Meeting on Science, Quality and Value of Laboratory Medicine was held on 11 December 2025 in Padua, immediately preceding the 7th European Federation of Clinical Chemistry and Laboratory Medicine (EFLM) Conference on the Preanalytical Phase. For organizational reasons, the meeting was structured in two parts, with the first held in December 2025 and the second scheduled for early 2026. The initiative, designed to better steer and promote the activities of all EFLM Committees and Divisions, represents a pivotal step toward overcoming fragmentation and silo-based cultures. By fostering a holistic vision that captures interactions among all EFLM Functional Units, the meeting supported the translation of value-based laboratory medicine principles into real-world practice. This collective opinion paper summarizes the lectures presented at the meeting, providing an overview of ongoing EFLM projects and future developments in value-based laboratory medicine. Importantly, the meeting also generated significant opportunities for collaboration and shared project development, underscoring the transition from isolated activities to a collaborative, value-driven approach.